Determinants of the performance of college teachers in region I - Estira, Victoriano Campos 1949- (1986)
This study was undertaken to identify the personal and institutional factors related to the performance of college teachers in research, extension and instruction in six public and six private tertiary institutions. Four hundred college teachers (213 from public and 187 from private colleges/universities) were asked to accomplish a questionnaire to gauge their performance in research and extension and were rated for teaching performance by administrators and students. Faculty members with high educational attainment outperformed those with low educational attainment in all the 3 basic functions of tertiary education.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: College teachers -- Philippines -- Ilocos Region